an Error Analysis on the Use Of Simple Past Tense in Writing Narrative Text of 11th Grade High School Students at SMK Swasta YPK Medan Academic Year 2022/2023 - Suhartini, Azaniah; Nurlaili, Nurlaili (Journal of Educational Research and Humaniora (JERH), 2024)
Simple past tense is an action or activity carried out by a subject in the past. Past tense refers to actions in the past and tells us all about their relationship with the present. The purpose of this research is to know types and causes of error on simple past tense. To know dominant error on the use of simple past tense in writing narrative text. To find out difficulties faced by students in comprehending simple past tense and narrative text. The researcher adopts a descriptive qualitative method. Carried out by gathering data from the natural environment without altering the situation. Data of this research is error made by students in written test of past tense. Data source is a writing test with the theme “My Holiday”. It consists of 55 words or more. Tests are distributed to 16 students of SMK SW YPK MEDAN. The researcher found 116 errors from writing test that the researcher carried out, it was found that the highest frequency of error that students made was mis formation about 78.45% errors, omission was 12.93% errors, selection was 5.17% errors, addition was 2.59% the last was mis ordering with 0.86%. the researcher also found that the highest error was caused by intralingual and the second highest was caused by interference.